The power of experiments : decision making in a data-driven world - Luca, Michael; Bazerman, Max H. (Cambridge, Mass. : The MIT Press, 2021)
"Have you logged into Facebook recently? Chosen a movie on Netflix? If so, you've probably been an unwitting participant in a variety of experiments--also known as randomized controlled trials--designed to test the impact of different online experiences. In this book, Michael Luca and Max Bazerman explain the importance of experiments for decision making in a data-driven world. They describe the central role experiments play in the tech sector, drawing lessons and best practices from the experiences of such companies as StubHub, Alibaba, and Uber. Moving beyond tech, Luca and Bazerman consider experimenting for the social good--different ways that governments are using experiments to influence to 'nudge' behavior ranging from voter apathy to school absenteeism."--
Breaking out of the lab. The power of experiments -- The rise of experiments in psychology and economics -- The rise of behavioral experiments in policymaking -- Experiments in the tech sector. From the behavioral insights team to Booking.com -- #AirbnbWhileBlack -- eBay's $50 million advertising mistake -- Deep discounts at Alibaba -- Shrouded fees at StubHub -- Market-level experiments at Uber -- The Facebook blues -- Experimenting for the social good. Behavioral experiments for the social good -- Healthy, wealthy, and wise -- The behavior change for good project -- The ethics of experimentation -- A final case for experiments and some concluding lessons.
Reprint. Originally published: 2020.
Includes bibliographical references (p. 189-201) and index.
Keywords: Economics -- Psychological aspects; Experimental economics; Decision making; Psychology